Pengaruh Pendidikan Kewirausahaan dan Model Pembelajaran TF-6M Terhadap Kompetensi Wirausaha Siswa: Survei pada Siswa XII Alfa Class Program Keahlian Bisnis Daring dan Pemasaran di SMK PGRI Subang Tahun Ajaran 2021/2022 - Utami, Anggi Annisa Nur; Supardi, Endang (Universitas Pendidikan Ganesha, 2022)
This study aims to determine entrepreneurship education, the TF-6M model and student entrepreneurial competence, as well as the influence of entrepreneurship education, the TF-6M model on student entrepreneurial interest and the effect of learning creative and entrepreneurial products on the entrepreneurial competencies of class XII BDP students at SMK PGRI Subang in the 2021 academic year. /2022. The research method used is a survey with a sample of 82 students. Data analysis in this study used multiple linear regression analysis with the results showing the recapitulation of the average score of respondents' responses regarding learning creative products and entrepreneurship was 4.06 (81.2%) while the TF-6M model was 4.27 (85.36). %), this number means that the Entrepreneurial Education variable (X1) and the TF-6M Model (X2) simultaneously affect the Y variable.